Answers

2015-09-24T05:31:23+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
35+ 39+ 43
equals to 117
0
  • Brainly User
2015-09-24T11:59:45+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
First number: x
Second number: x + 4 (four more than the first number)
Third number: (x+4) + 4   or   x+8  (four more than the second number)

Sum of the numbers = 117
(x) + (x+4) + (x+8) = 117
3x + 12 = 117
3x + 12 - 12 = 117 - 12
3x = 105
3x/3 = 105/3
x = 35

The numbers are:
 First: x = 35
Second number:  x + 4 = 35 + 4 = 39
Third number: (x + 4) + 4 = 35 + 8 = 43

To check:
35 + 39 + 43 = 117
0